A Mixed‐Valent Uranium Phosphonate Framework Containing UIV, UV, and UVI. Issue 34 (15th July 2016) - Chen, Lanhua; Zheng, Tao; Bao, Songsong; Zhang, Linjuan; Liu, Hsin‐Kuan; Zheng, Limin; Wang, Jianqiang; Wang, Yaxing; Diwu, Juan; Chai, Zhifang; Albrecht‐Schmitt, Thomas E.; Wang, Shuao
Abstract: It is shown that U V O2 + ions can reside at U VI O2 2+ lattice sites during mild reduction and crystallization process under solvothermal conditions, yielding a complicated and rare mixed‐valent uranium phosphonate compound that simultaneously contains U IV, U V, and U VI . The presence of uranium with three oxidation states was confirmed by various characterization techniques, including X‐ray crystallography, X‐ray photoelectron, electron paramagnetic resonance, FTIR, UV/Vis‐NIR absorption, and synchrotron radiation X‐ray absorption spectroscopy, and magnetism measurements. Abstract : Three's company : A complex uranium compound was synthesized by a redox‐active solvothermal reaction. It is the first phosphonate compound that contains three oxidation states of uranium simultaneously.